Evaluation of Psychological Work Environment's Effect on Workers' Productivity in Baghdad City - Kadium, Jameel; Abdul-Wahid, hala (Iraqi National Journal of Nursing Specialties, 2014)
Objective: To evaluate the psychological work environment's effect on the workers’ productivity in BaghdadCity industries at Al-Rusafa and Al-Karkh Sectors.Methodology: A descriptive evaluation design is employed throughout the present study from May 25th 2012through January 7th, 2014. A purposive (non probability) sample is selected for the study which includes (500)workers from industries at AL-Russafa and AL-Kerch sectors in Baghdad City. A questionnaire is constructed togather data which may assist to achieve the objective of the study. Content validity of the instrument isdetermined through eliciting the opinions of a panel of (10) experts and the reliability through a pilot study byusing internal consistency reliability which is determined through the computation of the Cronbach alphacorrelation coefficient of the scale on data gathered from workers. Data are analyzed through the applicationof descriptive statistical data analysis procedures of frequency, percentage, mean, weighted mean andstandard deviation and inferential statistical data analysis procedures of Cronbach alpha correlation coefficient,relative sufficiency, and multiple regression.Results: The findings depict that the psychological work environment is manifested as greatly psychologicalproblem creating one (43%); moderately psychological problem creating environment (49.4%) and problemfree environment. The vast majority of the workers has unfortunately experienced moderate (60.2%) and low(38.8%) levels of productivity as a result of the influence of its indicators.Recommendations: The study recommends that Occupational–oriented health education program withemphasis on psychological work environment, and its impact upon workers’ productivity can be constructedand implemented for workers on a wide-range scale. Further research can be conducted on large sample sizeand nation-wide.